Deskripsi Kesalahan Mahasiswa Dalam Membuktikan Suatu Grup Studi Pada Mahasisiwa Pendidikan Matematika Universitas Al Asyariah Mandar - Fatimah Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2013)
This study describes student errors in proving a particular operation is set to the group or not group by using the definition of the group, which is closed, assossiatif, the presence and absence of identity element inverse element. It is intended to determine the types of errors and mistakes, as well as the factors that cause students to make mistakes in proving a particular operation is set to the group or not group by using the group definition.